2005
DOI: 10.1021/cm0506151
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Physical Properties of Ternary Antimonide YbCrSb3

Abstract: The ternary rare-earth antimonide YbCrSb3 was prepared by arc-melting of the elements. Its structure was determined by single-crystal X-ray diffraction (Pearson symbol oP20, orthorhombic, space group Pbcm, Z = 4, a = 12.981(3) Å, b = 6.140(1) Å, c = 5.993(1) Å). YbCrSb3 is isostructural to LaCrSb3 and CeCrSb3, and extends the RECrSb3 series (previously known for RE = La, Ce, Pr, Nd, Sm, Gd, Tb, Dy) to the latest rare-earth member yet and to one that is essentially divalent instead of trivalent. Electrical resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 25 publications
1
28
0
Order By: Relevance
“…The only report of rare-earth substitution beyond Dy in RTSb 3 is that reported for YbCrSb 3 . In YbCrSb 3 , however, the ionic radius of Yb ($1.33 Å ), was found to be similar to Sm 3+ (1.27 Å for a coordination number of 9), which hints at divalent Yb 2+ [19]. The reported unit cell volume of YbCrSb 3 is 477.6(2) Å 3 and near to that of SmCrSb 3 and 478.68(10) Å 3 [19].…”
Section: Article In Pressmentioning
confidence: 89%
See 3 more Smart Citations
“…The only report of rare-earth substitution beyond Dy in RTSb 3 is that reported for YbCrSb 3 . In YbCrSb 3 , however, the ionic radius of Yb ($1.33 Å ), was found to be similar to Sm 3+ (1.27 Å for a coordination number of 9), which hints at divalent Yb 2+ [19]. The reported unit cell volume of YbCrSb 3 is 477.6(2) Å 3 and near to that of SmCrSb 3 and 478.68(10) Å 3 [19].…”
Section: Article In Pressmentioning
confidence: 89%
“…Given that variations in stoichiometry have been identified in the RTSb 3 series [11,18,19] and may be a cause for discrepancies in magnetic order [5,[13][14][15][16][17], in this study we start with a detailed structural evaluation of the RVSb 3 (R ¼ La-Nd, Sm, Gd-Dy) flux-grown single crystals. The starting structural parameters were taken from the reported CeTSb 3 (T ¼ Cr, V) structure, Ref.…”
Section: Structure Of Rvsbmentioning
confidence: 99%
See 2 more Smart Citations
“…They have compared the strong spin correlations observed in LaCrSb 3 with those observed in manganites and suggested that both local moment and itinerant spins coexist in LaCrSb 3 . Recently, Crerar et al [11] have reported that in YbCrSb 3 , Cr orders at 240 K and Yb assumes a charge state close to 2 þ . It appears that correlated ion like Yb influences the magnetic ordering of Cr spins.…”
Section: Introductionmentioning
confidence: 99%